Precauções específicas : vivências de pacientes internados - Jesus, Josélia Batista de (2017)
“Specific precautions” are measures taken during the hospitalization of patients with a suspect or a diagnosis of air or contact transmitted diseases. Those measures involve the utilization of private rooms or individual protection equipment and aim at preventing cross infection. The permanence in precaution can provoke different emotions in these individuals. This study’s goal is to learn about the perception, significance and repercussions of the specific precautions to the hospitalized patient. It is a qualitative study, using the clinical qualitative methodology and the theoretical references of vulnerability. For the data collection stage, semi-directed interviews were utilized, and the data was analyzed through the thematic model of the content analysis. It has been identified three thematic units: “received orientation”, “perceptions about the private room”, and the “stigma associated with the condition of ‘isolation’”. Under “received orientation”, it has been observed a lack of information and mistakes about the real cause for implementing the precautions. In the unit “perceptions about the private room”, it has been identified not only favorable perceptions, like privacy, not having to share a room, and the sensation of being more protected and being better served, but also unfavorable ones, like feelings of despair, anguish and boredom for being alone and restricted to their room. In the last unit, “stigma associated with the condition of ‘isolation’”, it has been identified embarrassment related to the stigma of being in a unit called “isolation”, and fear for being segregated from the other patients and from their families. It is considered that this study can contribute to health services by broadening their vision beyond the controlling of the dissemination of microorganisms. It is perceived that the information offered to the patient is not adequate, varying from the total lack of information to mistaken justifications, which can contribute for the non-engagement of the patient and their families in the adoption of necessary measures. In addition, the hospitalization in specific precaution has caused in the interviewed patients the sensation of receiving better assistance, but also caused feelings of loneliness and anguish, as well as reinforced the perception of stigma, which in turn intensified their vulnerability.